Piezoelectric field enhancement in III–V core–shell nanowires. (May 2015) - Al-Zahrani, Hanan Y.S.; Pal, Joydeep; Migliorato, Max A.; Tse, Geoffrey; Yu, Dapeng
Abstract: Linear and quadratic piezoelectric coefficients of wurtzite III–V (GaP, InP, GaAs and InAs) semiconductors are calculated using ab-initio density functional theory. We show that the predicted magnitude of such coefficients is much larger than previously reported and of the same order of magnitude as those of III-N semiconductors. In order to show the applicability of wurtzite III–V semiconductors as piezoelectric materials, we model the bending distortion created on a nanowire by an atomic force microscope tip. We calculate the dependence of the piezoelectric properties of both homogeneous and core shell wurtzite III–V semiconductor structures on the induced deflection. We show that a number of combinations of III–V materials for the core and the shell of the nanowires can favor much increased voltage generation. We observe the largest core voltages in core/shell combinations of InAs/GaP, InP/GaP, GaP/InAs and GaP/InP which are predicted to be 3 orders of magnitude larger than the typical values of ±3 V in homogeneous nanowires. Also considering properties such as voltage generation, bandgap discontinuity and mobility, III–V wurtzite core–shell nanowires are candidates for high performance components in piezotronics and nanogeneration. Graphical abstract: Highlights: We explore the strain dependence of the piezoelectric effect in wurtzite III–V (GaP, InP, GaAs and InAs) semiconductors. We report the predicted magnitude of the piezoelectric coefficients is much larger than previously reported and of the same order of magnitude as those of III-N semiconductors. We model the bending distortion created on a nanowire by an atomic force microscope tip. We calculate the dependence of the piezoelectric properties of both homogeneous and core shell wurtzite III–V semiconductor structures on the induced deflection. III–V Wurtzite core–shell nanowires are candidates for high performance components in piezotronics and nanogeneration.